Pemberdayaan Kelompok PKK melalui Ecosmart Farming dalam Mengubah Limbah Pembalut untuk Budidaya Tanaman dan Upaya Carbon Capture Berbasis Iot - Fatmawati, Lilis; Ikhtisholiyah, Ikhtisholiyah; Rusmanto, Didik Eko; Yaqin, Nur; Widayanti, Ameliya; Masyrofi, Mohammad Iqbal Faza (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Sanitary pads are one of the main necessities for women during menstruation, which generally occurs every month. Industrial cities such as Gresik have high levels of air pollution due to emissions from factories. The implementation of an IoT-based EcoSmart Farming program can help improve air quality through greening and improve soil quality with better planting media. The objectives of this activity are to increase knowledge and skills in sanitary napkin waste management and food safety, as well as plant monitoring with IoT sensors through a website. Methods: This activity consists of training, including education, demonstrations, discussions, and question and answer sessions. The activity began with SAP preparation and a contract with the Cerme Lor Village. The implementation stage started with a pre-test questionnaire, education on sanitary napkin waste management and food safety. This was followed by simulations and demonstrations of sanitary napkin waste management and how to monitor plants with IoT sensors. At the end of the activity, participants were asked to fill out a post-test questionnaire. Results: The activity resulted in an increase in the knowledge and skills of PKK mothers in sanitary napkin waste management and how to monitor plants with IoT sensors. The overall category of participants' knowledge improved from poor to adequate and good. Conclusion: This activity is a first step towards improving the health of PKK mothers in Cerme Lor Village through independent sanitary napkin waste processing, enabling health cadres to intervene quickly to reduce plastic waste.